The Influence of Participatory Digital Green Marketing on Tourists’ Pro-Environmental Behavior through Psychological Mechanisms - Wati Susilawati; Risma Muhamad Ramdani; Jeri Cahyadi Saputra; Dudi Amarullah (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Growing concerns about environmental sustainability in tourism destinations have highlighted the need to understand factors that encourage tourists to engage in environmentally responsible behavior. The purpose of this study is to examine the influence of participatory digital green marketing on tourists’ pro-environmental behavior in the context of sustainable tourism, as well as to investigate the mediating roles of environmental knowledge, environmental awareness, and place identity in explaining the psychological mechanisms that drive sustainable behavior. Using a quantitative explanatory survey and Structural Equation Modeling (SEM) analysis, the article discusses the integration of green marketing with community-based tourism narratives. Data results reveal that participatory digital green marketing has a positive impact on all studied variables. However, the main findings indicate that only environmental awareness significantly mediates the relationship between participatory digital green marketing and tourists’ pro-environmental behavior, whereas environmental knowledge and place identity do not. These results suggest that enhancing tourists’ environmental awareness through participatory digital engagement is the most effective mechanism for promoting environmentally responsible behavior in traditional tourist destinations. This study contributes a new model for sustainability-oriented marketing rooted in local culture.